Time matters: reviewing the care provided to patients admitted to hospital following an out-of-hospital cardiac arrest. (2nd February 2022) - Smith, Neil; Koomson, D'Marieanne; McPherson, Simon; Juniper, Mark
Abstract : The National Confidential Enquiry into Patient Outcome and Death reviewed the organisation of services and the quality of clinical care provided to patients who were admitted to hospital following an out-of-hospital cardiac arrest. The report looked at all four links in the 'chain of survival', covering the last link, in-hospital advanced life support and post-resuscitation care, in most detail.